Hesperidin associated with continuous and interval swimming improved biochemical and oxidative biomarkers in rats - de Oliveira, David Michel [UNESP]; Dourado, Grace Kelly Zanotti Simoes [UNESP]; César, Thaís Borges [UNESP] (Taylor & Francis, 2013)
Background: Citrus flavonoids, such as hesperidin, have shown therapeutic properties that improve hyperglycemia and insulin resistance, and decrease blood serum lipids and inflammation. The current investigation studied the effects of hesperidin supplementation associated with continuous and interval swimming on the biochemical parameters (glucose, cholesterol and triglycerides), and oxidative stress markers (TBARS and DPPH) in rats.Methods: The animals (n = 60) were randomly divided in six groups: negative (C) and positive control (CH) for hesperidin supplementation, and continuous or interval swimming without (CS and IS) or with hesperidin supplementation (CSH and ISH). Hesperidin was given by gavage for four weeks (100 mg/kg body mass) before the exercise. Continuous swimming was performed for 50 min with loads from 5% to 8 % of body weight from the first to fourth week, while interval swimming training was performed for 50 min in sessions of 1 min of swimming followed by 2 min of resting, carrying loads from 10% to 15, 20 and 25% from the first to fourth week. At the end of the experiment, blood serum samples were draw to perform analysis of glucose, total cholesterol, HDL-C and triglycerides. Oxidative biomarkers were evaluated by lipid peroxidation (TBARS) and antioxidant capacity assay (DPPH) of the blood serum.Results: There was a continuous decline of serum glucose from C (100%) > CH (97%) > CS (94%) > CSH (91%, p < .05), IS (87%, p < .05) > ISH (80%, p < .05), showing a combined beneficial effect of hesperidin and swimming. Also, continuous or intermittent swimming with hesperidin supplementation lowered total cholesterol (-16%, p < .05), LDL-C (-50%, p < 0.05) and triglycerides (-19%, p < 0.05), and increased HDL-C (48%, p < .05). Furthermore, hesperidin enhanced the antioxidant capacity on the continuous swimming group (183%, p < .05) and lowered the lipid peroxidation on the interval swimming group (-45%, p < .05).Conclusions: Hesperidin supplementation per se, or in combination with swimming exercise protocols, improved the biochemical profile and antioxidant biomarkers evidencing that the use of flavanones may enhance the health benefits promoted by exercise. © 2013 de Oliveira et al.; licensee BioMed Central Ltd.
Keywords: Antioxidant; Blood serum biomarkers; Continuous swimming; Hesperidin; Interval swimming; Rat; Animalia; Citrus; Rattus